Helicobacter pylori contributes to GC progression, possibly via the MSTRG.10627.1/miR-142-5p/ADAMTS5 pathway - Yin, Zhipeng; Xiang, Jianwei; Guo, Pengbo; Zhang, Nianli; Lv, Xiaoqian; Wang, Yu; Wu, Yi; Zhang, Nianhua; Lv, Gang; Zhao, Yinghui (Frontiers in Microbiology, 2026)
BackgroundHelicobacter pylori (H. pylori) is a class I carcinogen that induces gastric cancer (GC). The mechanisms underlying its induction of GC are not fully understood. The role of the MSTRG.10627.1/miR-142-5p/ADAMTS5 pathway induced by H. pylori in GC was investigated in this study.MethodsRNA sequencing and bioinformatics analysis were used to screen a regulatory pathway lncRNA-miRNA-mRNA. The dual luciferase reporter was used to evaluate interactions between the lncRNA and the miRNA or between the miRNA and the mRNA. The cellular biological effects of ADAMTS5 were detected using clonogenic formation and cell migration assays. A western blot was used to assess the protein expression of the pathway. The role of ADAMTS5 in tumor growth and metastasis was validated in nude mice using subcutaneous and tail vein injections.ResultsA regulatory axis lncRNA (MSTRG.10627.1)-miRNA (miR-142-5p)-mRNA (ADAMTS5) with the highest correlation coefficient was screened out. The combinations between MSTRG.10627.1 and miR-142-5p or between miR-142-5p and ADAMTS5 were verified. The expression of ADAMTS5 was down-regulated by H. pylori (p < 0.05). The proliferation, migration, and invasion of GC cells were increased by down-regulation of ADAMTS5 (p < 0.05); however, the proliferation, migration, and invasion of GC cells were inhibited by the overexpression of ADAMTS5 (p < 0.05). After silencing of ADAMTS5 in GC cell lines, western blot showed that the expression of PI3K protein and the phosphorylation level of AKT protein were increased (p < 0.05), and the expression of tumor suppressor p53 was inhibited (p < 0.05). However, overexpression of ADAMTS5 in GC cells induced the opposite results (p < 0.05). The results of the subcutaneous tumor model in nude mice showed that tumor weight and volume increased after silencing of ADAMTS5 (p < 0.05). The metastasis of GC cells in the metastatic tumor model was inhibited by overexpression of ADAMTS5 (p < 0.05).ConclusionThe expression of ADAMTS5 was down-regulated by H. pylori through regulating a probable pathway (MSTRG.10627.1-miR-142-5p-ADAMTS5). Moreover, down-regulated ADAMTS5 induced PI3K protein, up-regulated phosphorylated AKT protein, and down-regulated p53, which plays an important role in the induction of GC.